Step
*
1
of Lemma
rexp-non-decreasing
1. a : ℝ
2. b : ℝ
3. a ≤ b
4. e^a + (b - a) = (e^a * e^b - a)
⊢ e^a ≤ e^b
BY
{ ((Assert (a + (b - a)) = b BY Auto) THEN (RWO "-1" (-2) THENA Auto) THEN (RWO "-2" 0 THENA Auto)) }
1
1. a : ℝ
2. b : ℝ
3. a ≤ b
4. e^b = (e^a * e^b - a)
5. (a + (b - a)) = b
⊢ e^a ≤ (e^a * e^b - a)
Latex:
Latex:
1.  a  :  \mBbbR{}
2.  b  :  \mBbbR{}
3.  a  \mleq{}  b
4.  e\^{}a  +  (b  -  a)  =  (e\^{}a  *  e\^{}b  -  a)
\mvdash{}  e\^{}a  \mleq{}  e\^{}b
By
Latex:
((Assert  (a  +  (b  -  a))  =  b  BY  Auto)  THEN  (RWO  "-1"  (-2)  THENA  Auto)  THEN  (RWO  "-2"  0  THENA  Auto))
Home
Index